The PLA Navy - Gao, Xiaoxing; Weng, Saifei; Zhou, Dehua; Sun, Yanhong; Chen, Liangwu; Chen, Gang (Series of Chinese army, 2012)
What kind of an army is the PLA? What stage of development are the various branches of the Chinese armed forces in? What a level of development does military weapons and equipment have reached?These questions have spurred a lively discussion of great concern to the international community and some overseas mediaFor this reasonWang wei Xu dingxin believe that writing a vivid and accurate series of the Chinese armyfor both domestic and foreign readerswould be very perinentThe PLA Navyis one of these in the first series of books on the Chinese Army